(untitled) (SMART MOVES JOURNAL IJOSCIENCE, 2022)
Flyovers or grade separators are bridges built over a traffic intersection to allow people to literally ‘fly over’ the traffic. Flyovers were required on ring roads meeting arterial interchanges, over rivers (“where they are called bridges") or across railway lines. In the past, some flyovers were constructed in different urban locations in India.Thus it is necessary to construct the flyover which is sustainable. Quality and structural design matters a lot, otherwise constructing a flyover is just the waste of money. This paper present the overview of flyover, the constructional procedure of flyover as well as the types of load on the flyover.